New synonyms and typifications of Stillingia (Euphorbiaceae) - Athiê-Souza, Sarah Maria; de Melo, André Laurênio; Da Silva, Marcos José; de Sales, Margareth Ferreira (Phytotaxa, 2016)
In this manuscript two new synonyms for Stillingia species are proposed. Stillingia dusenii is synonymized with Stillingia bodenbenderi, and Stillingia pietatis is synonymized united with Stillingia acutifolia. In addition, the lectotypes are proposed for 26 names.